If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 3) + (3x + 8) = 0 Reorder the terms: (3 + 2x) + (3x + 8) = 0 Remove parenthesis around (3 + 2x) 3 + 2x + (3x + 8) = 0 Reorder the terms: 3 + 2x + (8 + 3x) = 0 Remove parenthesis around (8 + 3x) 3 + 2x + 8 + 3x = 0 Reorder the terms: 3 + 8 + 2x + 3x = 0 Combine like terms: 3 + 8 = 11 11 + 2x + 3x = 0 Combine like terms: 2x + 3x = 5x 11 + 5x = 0 Solving 11 + 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 5x = 0 + -11 Combine like terms: 11 + -11 = 0 0 + 5x = 0 + -11 5x = 0 + -11 Combine like terms: 0 + -11 = -11 5x = -11 Divide each side by '5'. x = -2.2 Simplifying x = -2.2
| 5e+13=7e-21 | | 8x-6=4x | | 13x=32+5 | | 4(g+3)-12=116 | | 5+2n=3n-16 | | b(2b-3)=10 | | 10y-2=7b-7.4 | | 2x+3y=4x+6y | | r(r-3)=4 | | 52=(2x+1)(x+1) | | 24-10x=x^2 | | 52=bh | | p(p+5)=36 | | 3x-2(6)= | | 4x-1=8x-9 | | 5(x-8)=10 | | 0.01x^3+1.8x^2-45x=120 | | 8x-8+1=-15 | | 0.01x^3+1.8x^2-45x=0 | | 3(5x-1)=12 | | -72x^7-8x^6= | | 3x+4x=91 | | 27=15a-2 | | 8-[8(-7+2)-2]= | | 0.01x^3-1.8x^2+165x=0 | | (8x)+(9x+5)=90 | | 9s^2-15s= | | 2y^2-5y-6=0 | | 3t-6=9 | | 3a+10=4(a+2)-.5a | | 6p-8(p-6)+2(q-6)= | | 3-4d=6d-17 |